The Influence of Learning Facilities and Motivation on Achievement Study Student Class X in Christian Vocational School in Tombatu - Lumapow, Harold R; Sumual, Shelty D.M.; Tuerah, Philotheus E A; Kambu, Kornelius; Sauyai, Stanly F M; Ratumbuisang, Keith F (International Journal of Information Technology and Education, 2024)
This research aimed to determine whether or not there was an influence of learning facilities and motivation on the learning achievements of students in class X TJK, X Nursing Assistant, X AKL, and X ATPH (30 respondents). The results of this research show that the multiple linear regression analysis obtained the equation Y=80.501 + 0.007x1 + 0.048x2. Where learning facilities and motivation influence the learning achievements of class X students at Tombatu Christian Vocational School. The correlation results show a value of r = 0.241, proving that the influence of learning facilities and motivation on learning achievement is relatively strong. Then for the F test, Fcount = 4,296 > Ftable = 3.35. The results obtained state that there is a significant influence on learning facilities and motivation on the learning achievements of class X students at SNK Tombatu Christian. The influence of learning facilities (x1) and student motivation (x2) influences learning achievements (Y) by 24%, the remainder is influenced by other factors. This research concludes that learning facilities and motivation influence the learning achievements of class X students at Tombatu Christian Vocational School, both simultaneously and partially.